Translation of Registers on the Friday Sermon at Nabawi Mosque - Nisa, Yunia Makin Aninda Fiqrotin; Anis, Muhammad Yunus (Institut Agama Islam Negeri (IAIN) Metro, 2023)
This research uses the material object of the Friday sermon, namely the translation of the sermon register of the scholar Ash-Shaikh Dr. Abdul Muhsin Al-Qosim. Each language has specific characteristics or is different from other languages. This research aims to find out the register of the Friday sermon of Ash-Sheikh Dr. Abdul Muhsin Al-Qosim at the Nabawi Mosque. The method used in this research is the descriptive qualitative method. Data were collected using listening techniques and data transcription in processing the data; the data was processed using the analysis model, namely Miles & Huberman. The result of this study is the existence of language registers contained in three perspectives: religious terminology, code mix, and language function. These three aspects are register or language variation forms, with details of seven categories in religious terminology, code mix (words and phrases), and five types of language functions.